Serrated Pathway Adenocarcinomas: Molecular and Immunohistochemical Insights into Their Recognition - Gurzu, Simona (Public Library of Science, 2013)
INTRODUCTION: Colorectal adenocarcinomas (CRC) developed through serrated pathway seem to present particular behavior compared with the non-serrated ones, but recognition of them is difficult to do. The aim of our paper was to establish some criteria to facilitate their identification. MATERIALS AND METHODS: In 170 consecutive CRCs, we performed immunohistochemical staining with Cytokeratin 7 (CK7) and Cytokeratin 20 (CK20) and also with p53 and MLH-1. At the same time, we analyzed BRAF and K-ras mutations and the microsatellite status of CRC. RESULTS: 26.47% of cases expressed CK7, and 16.47% were CK20-negative. Diffuse positivity for CK7 was associated in the proximal colon with CK20 negativity or weak positivity, BRAF mutations, lack of K-ras mutations, and p53 and MLH-1 negativity. All these cases were microsatellite-unstable and were diagnosed in stage II. Those cases from the distal colon and rectum that expressed CK7 were K-ras-mutated and had low p53 index and MLH-1 positivity, independent of the CK20 expression. CONCLUSIONS: CK7, associated with MLH-1 and p53 expression, and also with the microsatellite status, BRAF and K-ras pattern, might be used to identify the CRC potentially going through serrated pathway. The serrated pathway adenocarcinomas of the proximal colon that do not display the morphological features of this pattern are more frequent CK7+/p53−/MLH-1−/BRAF-mutated/K-ras-wt/MSI cases, but those located in the distal colorectal segments seem to be CK7+/CK20+/p53−/MLH-1+/BRAF wt/K-ras-mutated/MSS cases.